1996
DOI: 10.1021/jm9601967
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of 2β-Alkenyl Penam Sulfone Acids as Inhibitors of β-Lactamases

Abstract: A general method for synthesis of 2 beta-alkenyl penam sulfones has been developed. The new compounds inhibited most of the common types of beta-lactamase. The level of activity depended very strongly on the nature of the substituent in the 2 beta-alkenyl group. The inhibited species formed with the beta-lactamase from Citrobacter freundii 1205 was sufficiently stable for X-ray crystallographic studies. These, together with UV absorption spectroscopy and studies of chemical degradation, suggested a novel react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 32 publications
(82 reference statements)
0
44
0
Order By: Relevance
“…Inhibition with Ro 48-1220 was as effective as tazobactam for TEM-1 and SHV-1, with IC 50 s within 0.03 M for both enzymes. Most class C enzymes tested were inhibited at lower concentrations of Ro 48-1220 than of tazobactam (IC 50 range approximately 2-to 30-fold lower) (367,422). The IC 50 s for X. maltophilia and Bacteroides fragilis class B enzymes were 24 and 200 M, in comparison to 4 and Ͼ10 mM for tazobactam (367).…”
Section: Penicillin and Cephalosporin Sulfone Derivativesmentioning
confidence: 94%
See 1 more Smart Citation
“…Inhibition with Ro 48-1220 was as effective as tazobactam for TEM-1 and SHV-1, with IC 50 s within 0.03 M for both enzymes. Most class C enzymes tested were inhibited at lower concentrations of Ro 48-1220 than of tazobactam (IC 50 range approximately 2-to 30-fold lower) (367,422). The IC 50 s for X. maltophilia and Bacteroides fragilis class B enzymes were 24 and 200 M, in comparison to 4 and Ͼ10 mM for tazobactam (367).…”
Section: Penicillin and Cephalosporin Sulfone Derivativesmentioning
confidence: 94%
“…C-2/C-3-substituted penicillin and cephalosporin sulfones. ␤-Lactamase inhibitors with C-2 substitutions have shown efficacy against TEM-and SHV-type enzymes, including ESBLs (367,422). The acrylonitrile derivative Ro 48-1220 (Fig.…”
Section: Penicillin and Cephalosporin Sulfone Derivativesmentioning
confidence: 99%
“…Richter et al demonstrated that Ro 48-1220, the most active inhibitor from this class of compounds, enhanced the action of ceftriaxone against a broad selection of organism producing β-lactamases, including strains of cephalosporinase-producing Enterobacteriaceae [25]. In a diff erent study, Ro 48-1220 was at least 15 times more eff ective than tazobactam against the class C enzymes and reduced the MIC values of ceftriaxone and ceftazidime against the class A plasmid-mediated β-lactamases; less potency was exerted towards SHV-type β-lactamases [26].…”
Section: β-Alkenyl Penam Sulfonesmentioning
confidence: 99%
“…Using 20 well-characterized positive and negative control strains, the inhibitor-based test showed the potential for the detection of organisms producing plasmid-mediated AmpC ␤-lactamases of cefotetan in combination with LN-2-128 and 48-1220. LN-2-128 and 48-1220 are inhibitors of class A ␤-lactamases in addition to AmpC ␤-lactamases (4,22). A novel AmpC ␤-lactamase inhibitor, Syn 2190 (Naeja Pharmaceutical Inc., Edmonton, Alberta, Canada), does not inhibit class A ␤-lactamases (18).…”
mentioning
confidence: 99%